If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -59 + -9x = 46 + -16x Solving -59 + -9x = 46 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. -59 + -9x + 16x = 46 + -16x + 16x Combine like terms: -9x + 16x = 7x -59 + 7x = 46 + -16x + 16x Combine like terms: -16x + 16x = 0 -59 + 7x = 46 + 0 -59 + 7x = 46 Add '59' to each side of the equation. -59 + 59 + 7x = 46 + 59 Combine like terms: -59 + 59 = 0 0 + 7x = 46 + 59 7x = 46 + 59 Combine like terms: 46 + 59 = 105 7x = 105 Divide each side by '7'. x = 15 Simplifying x = 15
| 4x+12=-84-8x | | 6x+11=92-3x | | 153-4x=23x+15 | | t^2+t-2=0 | | -7-6x=9-10x | | x+y-3=0 | | 2x-2=12x-112 | | -4-3d-x=-16 | | 5x+24=13x-56 | | 2x+52=6x+12 | | 16x+15=8x+44 | | 15m-9-6m=9 | | -6x-4-5c=10+8 | | 2+3x=5+2x | | 75+2x=15-5x | | 9+2w=15 | | 2h+11=67 | | 80+10c=150c+5 | | 21+5x=15+11x | | 7x+3+x=16+3 | | 7c+3+x=16+3 | | 74+5x=9x+18 | | 3(x-2)+41=-4x | | -3x-2(6-9x)=10x-45 | | 3x+8=56-3x | | 10+3x=16+x | | 6y-8=-3y-35 | | u+u+u=99 | | 5k+4=15 | | 6x+25=16x-55 | | x+x(.1)=23.75 | | 12x-9=10x-5 |